The Examination of ESAT-6, CFP-10, MPT-64 Antigens of Mycobacterium tuberculosis in Urine of Pediatric Tuberculosis Patient with Immunochromatography to Support the Diagnosis - Budiarti, Anita; Nugraha, Jusak; Widodo, Agung Dwi Wahyu (Folia Medica Indonesiana, 2018)
Tuberculosis in children is often a systemic complication because of their imperfect cellular immune system. ESAT-6, CFP-10, and MPT-64 are small molecular dominant antigens secreted by Mtb into the blood and filtered by the kidneys into urine. The high proportion of children with TB cases according to the Ministry of Health of the Republic of Indonesia in 2013 was 7.9%-12%. Diagnis is difficult to establish with sputum and blood samples. Therefore, it is necessary to support the diagnosis using urine samples with ICT rapid test. The purpose of this study was to determine the examination of Mtb ESAT-6, CFP-10, and MPT-64 antigens in the urine of pediatric TB patients with ICT to support the diagnosis. The method used was analytic observation with case control design. The results of the study showed that 32 of the urine of children with TB who were examined with ICT, 22 showed ESAT-6, CFP-10, and MPT-64 positive and 10 negative. Whereas, from 32 urine of healthy children, 25 were negative and 7 were positive. Analysis results showed 95% confidence (CI), p = 0.0002 (p <0.05), 78% specificity and 68.8% sensitivity compared to TB diagnosis from pediatricians. As a conclusion, Mtb ESAT-6, CFP-10, and MPT-64 antigens can be examined in the urine of pediatric TB patients with ICT to support the diagnosis.